Robert Rypon and the Creation of London, British Library, MS Harley 4894: A Master Preacher and his Sermon Collection. Issue 1 (October 2015) - Johnson, Holly
Abstract : London, British Library, MS Harley 4894 is a handsome manuscript containing the fifty-nine extant sermons of Master Robert Rypon, a monk of Durham priory in England at the turn of the fifteenth century. Complete with illuminated initials and a detailed index, this sermon collection attests not only to the high regard in which Rypon was held as a preacher but to the resources that the monks were willing to expend in preserving his sermons and making them accessible to current and future readers. Like a model sermon collection the sermons are arranged in liturgical order, and the manuscript employs a system of marginal annotations which, together with its index, is designed to help readers navigate the collection. This article presents evidence, palaeographical and textual, suggesting that Rypon himself is the mastermind behind the creation of Harley 4894.